2021
DOI: 10.3390/ijms221810107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BMI-1 Induces Apoptosis through Downregulation of DUB3-Mediated Mcl-1 Stabilization

Abstract: BMI-1, a polycomb ring finger oncogene, is highly expressed in multiple cancer cells and is involved in cancer cell proliferation, invasion, and apoptosis. BMI-1 represents a cancer stemness marker that is associated with the regulation of stem cell self-renewal. In this study, pharmacological inhibition (PTC596) or knockdown (siRNA) of BMI-1 reduced cancer stem-like cells and enhanced cancer cell death. Mechanistically, the inhibition of BMI-1 induced the downregulation of Mcl-1 protein, but not Mcl-1 mRNA. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…The current study is in agreement with previous research that indicated that Akt/GSK3β signaling is required for MCL-1 S159 phosphorylation and degradation [48]. Certain deubiquitinases such as USP9X [49], JOSD1 [50], USP13 [51], DUB3 [52] and Ku70 [53] have been demonstrated to stabilize MCL-1. However, the molecular mechanisms by which these deubiquitinases stabilize MCL-1 are not fully understood.…”
Section: Discussionsupporting
confidence: 93%
“…The current study is in agreement with previous research that indicated that Akt/GSK3β signaling is required for MCL-1 S159 phosphorylation and degradation [48]. Certain deubiquitinases such as USP9X [49], JOSD1 [50], USP13 [51], DUB3 [52] and Ku70 [53] have been demonstrated to stabilize MCL-1. However, the molecular mechanisms by which these deubiquitinases stabilize MCL-1 are not fully understood.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to the effect of PRIMA-1 MET , our results are in line with the study by Patyka M et al, reporting that the drug is effective in preventing the propagation of neurospheres originating from patientderived glioblastoma cells [84]. Similarly, this ability has been also recently described for PTC596 [87,88], suggesting that the modulation of BMI-1 might be a promising approach to curing cancer patients.…”
Section: Discussionsupporting
confidence: 91%
“…Inhibition of Bmi-1 can promote the expression of p14 ARF ( p19 ARF ), and p14 ARF (p19 ARF ) can antagonize the ubiquitin-protein ligase MDM2 to stabilize p53 and cause apoptosis. This phenomenon has been reported in many studies [ 29 , 96 , 97 ]. A second pathway involves the inhibition of Bmi-1, causing abnormal mitochondrial function and increasing the level of ROS, leading to apoptosis.…”
Section: Bmi-1-targeted Processes In Cancersupporting
confidence: 71%